Kepemimpinan Kepala Madrasah dalam Meningkatkan Etos Kerja Guru di MTsN 1 Kota Bima - M. Adnan (Literasi: Jurnal Pendidikan Guru Indonesia, 2023)
This research aims: 1) to analyze the leadership of the madrasa head at MTsN 1 Bima City, 2) to analyze the work ethic of teachers at MTsN 1 Bima City, and 3) to analyze the factors that encourage and inhibit teacher work ethic at MTsN 1 Bima City. This research is qualitative research (case study). The research instrument uses observation guidelines and interview guidelines. Data processing and analysis techniques are carried out through three stages, namely data reduction, data presentation, and drawing conclusions and data verification. The results of the research show 1) The leadership of the Head of MTsN 1 Bima City is quite good because he upholds responsibility with full trust, 2) The work ethic of MTsN 1 Bima City teachers is well recommended, because they have displayed performance and various kinds of efforts made to achieve learning goals , 3) Supporting factors for work ethic (discipline, teacher's personality in carrying out their duties, example and firmness of the school principal. Inhibiting factors, it appears that there are still many teachers who teach normally, namely using the lecture method only, so that students' interest in studying seriously decreases.